Tanggung Gugat Direksi BUMD atas Keputusan yang Merugikan Keuangan BUMD - Roni Fahmi* (Universitas Airlangga, 2019)
BUMD is a business entity that all or most of its capital is owned by the region, and was established with the aim of providing benefits for the development of the regional economy in general, organizing public benefits in the form of providing quality goods and / or services for the fulfillment of the livelihood of the community according to conditions, characteristics, and the potential of the area concerned, based on good corporate governance. Management / management of BUMD can not be separated from the role of directors, because directors are BUMD organs responsible for the management of BUMD for the interests and purposes of BUMD, and represent BUMD both inside and outside the court. The problems in this study are about how the scope of accountability of BUMD directors in corporate activities and how to form the accountability of BUMD directors for decisions that are detrimental to BUMD finance. This research is expected to be able to know, describe and analyze the relationship between the scope of accountability with corporate activities and the relationship between the form of accountability with decisions that cause losses.